Institutional priorities and budgeting strategies affecting the collecting development of the UPLB Libraries - Maglinao, Erlinda L.; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study looks into the institutional priorities of the seven colleges of the University of the Philippines Los Baños (UPLB), the budgeting practices employed by their libraries, and which of these priorities and practices affect their collection development programs. The data were obtained using interviews with the seven college deans and twelve librarians-in-charge.
The study shows that all UPLB colleges consider instruction as their first priority, followed by research and extension. These institutional priorities are communicated to the libraries, primarily through meetings with and reports and brochures sent to the librarians. However, a more effective linkage between the two groups needs to be put in place. Communicating the information on institutional priorities must be coupled with the needed resources to enable the libraries to support these priorities. On the other hand, the librarians must be more aggressive and persuasive in presenting the needs and the budgetary requirements of their library to the college administration. It is observed that this is not actively pursued by most UPLB library. Not all librarians-in-charge employ budgeting practices to get more support for the libraries. They are constrained to apply budgeting practices, primarily because the libraries do not have any specific and regular budget allocation for their operation. Nevertheless, most librarians recognize the need to improve their collections. Moreover, they are aware of strategies which, when implemented, could help in collection development. However, it still needs more aggressiveness and persuasion on the part of the librarians to sell and market the services that the libraries provide.
It is recommended that college libraries be established in those colleges which continue to maintain reading rooms in order that a relocation of their resources from the Main library will be affected. A second recommendation is to allow all seven college libraries to be individually responsible for the library resources with overall supervision still resting with the University librarian. A third one explores the viability of forming strong alliances with the faculty and campus officials in order to support the library program.
The fourth recommendation calls for the maximization of the collections buying power through a careful planning of the collection budget, awareness of its users and institutional priorities, development program to include a Friends of the Library Group, fundraising activities, full and active participation in resource sharing arrangements, encouraging gifts and reduction in acquisitions program.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Finance; Library finance -- Philippines -- Laguna -- Los Baño